Performance improvements of tungsten and zinc doped indium oxide thin film transistor by fluorine based double plasma treatment with a high-K gate dielectric - Ruan, Dun-Bao; Liu, Po-Tsun; Chiu, Yu-Chuan; Yu, Min-Chin; Gan, Kai-Jhih; Chien, Ta-Chun; Chen, Yi-Heng; Kuo, Po-Yi; Sze, Simon M. (My University, 2018)
The electrical characteristics and XPS analysis for the amorphous tungsten and zinc doped indium oxide thin film transistor, which was performed with single or double different fluorine based remote plasma treatment, were investigated in this study. A high mobility TFT device with the tungsten doped channel was fabricated in the previous study, but there was an inevitable negative shift for the threshold voltage, which will be a limit for the application of systemic circuit design. Therefore, a double fluorine based remote plasma treatment process is proposed for the high electronegativity of fluorine element and its similar radius as oxygen, which can be used to terminate the donor-like oxygen vacancy. It may induce a positive shift of threshold voltage, while carrier concentration and field effect mobility might be maintained. As a result, the sample with CF4/N-2+O-2 plasma treatment exhibits a higher on/off current ratio of similar to 4.73 x 10(6), a lower sub-threshold swing value of 0.070 V/decade, and a lower interfacial trap density value of 5.21 x 10(11) eV(-1) cm(-2) than other samples, while there is even a desirable positive shift of threshold voltage and acceptable field effect mobility of 31.2 cm(2)/Vs. This research proposes an effective approach to improve the reliability characteristic and adjust the inevitable negative shift of threshold voltage without sacrificing the carrier mobility of device.
Keywords: Indium-tungsten-zinc-oxide; Thin-film transistors; Remote plasma treatment; High-k; Fluorine based double plasma treatment